If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 81 + -1x = -39 Solving 81 + -1x = -39 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-81' to each side of the equation. 81 + -81 + -1x = -39 + -81 Combine like terms: 81 + -81 = 0 0 + -1x = -39 + -81 -1x = -39 + -81 Combine like terms: -39 + -81 = -120 -1x = -120 Divide each side by '-1'. x = 120 Simplifying x = 120
| 4x-(3x-5)=2x+11 | | x-2.3=1.1 | | 2x-x=-5+3 | | a-12=36 | | 5+2x=3+x | | 8x-4+3x=7x+x-14 | | -12=28x+39 | | 4-y=26 | | 4m^2-6=46 | | 10=3c+1 | | 4x-9y=-68 | | 2s+4=10 | | -10+.25t=5 | | -10+.25t=-5 | | 9-2u=3 | | 4x+12-8x=24-6x | | 7a^2+80a+100=0 | | x^2+3x-18=9x-2 | | 1+(x+4)=8 | | 70=-7(-2--2) | | 7x+4y=34 | | 59-19=5(x-1) | | x^2-7x+14=4 | | 7x+4ty=34 | | 5b^2+9b+3=-2-9b^2 | | 34+4y-10=14y-12-4y | | 14=7-4x-32 | | x^2+3x-5x-15=0 | | 11=4-w | | y=x^2-5x-4 | | (2n+5)(n-4)=0 | | 20mn-15n= |